2014
DOI: 10.3928/19404921-20140127-02
|View full text |Cite
|
Sign up to set email alerts
|

Nurse and Patient Interaction Behaviors’ Effects on Nursing Care Quality for Mechanically Ventilated Older Adults in the ICU

Abstract: The study purposes were to 1) describe interaction behaviors and factors that may impact communication and 2) explore associations between interaction behaviors and nursing care quality indicators between 38 mechanically ventilated patients (≥60 years) and their intensive care unit nurses (n=24). Behaviors were measured by rating videotaped observations from the Study of Patient-Nurse Effectiveness with Communication Strategies (SPEACS). Characteristics and quality indicators were obtained from the SPEACS data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 55 publications
1
35
0
2
Order By: Relevance
“…Table 3 details the AAC interventions with high-technology computer-aided AAC strategies (Happ et al, 2004b;Happ et al, 2005; Rodriguez et al, 2016), ease or difficulties in communication (Happ et al, 2004b;Happ et al, 2005;Happ et al, 2014;Maringelli et al, 2013;Otuzoglu & Karahan, 2014;Rodriguez & Rowe, 2010, Rodriguez et al, 2016, communication success or effectiveness (Happ et al, 2014;Happ et al, 2016), initiation of communication (Happ et al, 2005), staff satisfaction (Maringelli et al, 2013;Miglietta et al, 2004), patient agitation and anxiety (Happ et al, 2016) and barriers to use (Happ et al, 2004b;Happ et al, 2014;Rodriguez et al, 2010;Rodriguez & Rowe, 2012). A variety of study designs were used which included some described as randomised controlled trials (RCT) (El-Soussi et al, 2014), randomised cluster trials (Happ et al, 2015), quasi-experimental (Happ et al, 2014;Otuzoglu & Karahan, 2014, Rodriguez et al, 2016, correlational (Nilsen et al, 2014), time-series (Rodriguez & Rowe, 2010) to pilot/feasibility studies (Happ et al, 2004b;Happ et al, 2005;Maringelli et al, 2013;Miglietta et al, 2004;Rodriguez et al, 2012). The studies described as randomised trials (El-Soussi et al, 2014;Happ et al, 2016) were treated as controlled or cohort analytic trials as the reported randomisation process was unclear.…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 3 details the AAC interventions with high-technology computer-aided AAC strategies (Happ et al, 2004b;Happ et al, 2005; Rodriguez et al, 2016), ease or difficulties in communication (Happ et al, 2004b;Happ et al, 2005;Happ et al, 2014;Maringelli et al, 2013;Otuzoglu & Karahan, 2014;Rodriguez & Rowe, 2010, Rodriguez et al, 2016, communication success or effectiveness (Happ et al, 2014;Happ et al, 2016), initiation of communication (Happ et al, 2005), staff satisfaction (Maringelli et al, 2013;Miglietta et al, 2004), patient agitation and anxiety (Happ et al, 2016) and barriers to use (Happ et al, 2004b;Happ et al, 2014;Rodriguez et al, 2010;Rodriguez & Rowe, 2012). A variety of study designs were used which included some described as randomised controlled trials (RCT) (El-Soussi et al, 2014), randomised cluster trials (Happ et al, 2015), quasi-experimental (Happ et al, 2014;Otuzoglu & Karahan, 2014, Rodriguez et al, 2016, correlational (Nilsen et al, 2014), time-series (Rodriguez & Rowe, 2010) to pilot/feasibility studies (Happ et al, 2004b;Happ et al, 2005;Maringelli et al, 2013;Miglietta et al, 2004;Rodriguez et al, 2012). The studies described as randomised trials (El-Soussi et al, 2014;Happ et al, 2016) were treated as controlled or cohort analytic trials as the reported randomisation process was unclear.…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…The included studies used a variety of AAC strategies but a meta-analysis to compare data across studies was not appropriate due to the heterogeneity of study designs and outcomes measures. The AAC strategies that were used were reported to reduce difficulty in communication (Happ et al, 2004b;Happ et al, 2005;Happ et al, 2014;Maringelli et al, 2013;Otuzoglu & Karahan, 2014), improve patient satisfaction in communication (El-Soussi et al, 2014;Miglietta et al, 2004;Rodriguez & Rowe, 2010;Rodriguez et al, 2012;Rodriguez et al, 2016), reduce patient frustration in communication (Rodriguez et al, 2016), increase communication interactions (Happ et al, 2014) and increase positive nurse behaviours such as smiling or giving preparatory information before a procedure (Nilsen et al, 2014).…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The uses of verbal and nonverbal interaction behaviors facilitate synergistic relationship (Nilsen et al, 2014). Good communication actually consists of many different sub-skills, from appropriate patterns of body language and eye contact to the ability to write clearly and accurately.…”
Section: Communicationmentioning
confidence: 99%
“…Accurate listening and the ability to follow instructions are especially important but are often ignored or taken for granted. Changes and environmental factors can contribute to communication breakdowns, misunderstandings, and difficulty recalling (Nilsen et al, 2014). …”
Section: Communicationmentioning
confidence: 99%